2021
DOI: 10.1111/bjhp.12513
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of protective behaviours during a nationwide lockdown in the wake of the COVID‐19 pandemic

Abstract: Objectives. Without pharmaceutical measures available, endorsement of protective behaviours, such as hygiene behaviours, social distancing, and adherence to recommended behaviours in case of symptoms is of key importance to curb the ongoing COVID-19 pandemic. Based on an extended version of the protection motivation theory, this study examined the role of perceived risks to oneself and to others, self-efficacy, response efficacy, and perceived social norms for intentions to and the endorsement of several prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 32 publications
8
43
0
Order By: Relevance
“…( Rubin et al, 2009 , Jørgensen et al, 2021 , Dryhurst et al, 2020 ) Greater perceived effectiveness of, and self-efficacy for, the behaviour were also associated with uptake in our study. ( Gibson Miller et al, 2020 , Jørgensen et al, 2021 , Rogers, 1975 , Scholz and Freund, 2021 , Seale et al, 2020 ) Having heard more about COVID-19 was associated with adopting a protective behaviour, similar to other research finding that media exposure was positively correlated with uptake of protective behaviours. ( Rubaltelli et al, 2020 ) This may be mediated by risk perception.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…( Rubin et al, 2009 , Jørgensen et al, 2021 , Dryhurst et al, 2020 ) Greater perceived effectiveness of, and self-efficacy for, the behaviour were also associated with uptake in our study. ( Gibson Miller et al, 2020 , Jørgensen et al, 2021 , Rogers, 1975 , Scholz and Freund, 2021 , Seale et al, 2020 ) Having heard more about COVID-19 was associated with adopting a protective behaviour, similar to other research finding that media exposure was positively correlated with uptake of protective behaviours. ( Rubaltelli et al, 2020 ) This may be mediated by risk perception.…”
Section: Discussionsupporting
confidence: 81%
“…Other studies have also found an association between uptake of preventive behaviours and being a parent. ( Lauri Korajlija and Jokic‐Begic, 2020 ) One study conducted in Switzerland found an association between uptake of preventive behaviours and older age ( Scholz and Freund, 2021 ); this has been a common pattern throughout the pandemic. ( Smith et al, 2021 , , xxxx ) Other studies conducted at the start of the pandemic found no association between age and uptake.…”
Section: Discussionmentioning
confidence: 99%
“…However, as mentioned in Section 1 , some studies support the view that risk perception does not always promote risk management behavior. Scholz and Freund [ 28 ] show that not risk perception but rather self-efficacy and response efficacy promote preventive behaviors. A study by Lin et al [ 29 ] also shows that self-efficacy contributes to preventive behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, males and those with less moral values showed lower compliance in Swiss adults [55], as did those with no worry about COVID-19 in Italian and French samples [57]. Further, perceived benefits and efficacy of protective measures have emerged as strong predictors of compliance across samples from a range of countries including Switzerland [58], Ethiopia [59], and China [60]. Nevertheless, we managed to capture a relatively heterogeneous sample, varying in age, gender, levels of education, pre-existing health conditions, and economic situation.…”
Section: Strengths and Limitationsmentioning
confidence: 94%